Rare‐Earth‐Free Mn30Fe20−xCuxAl50 Magnetocaloric Materials with Stable Cubic CsCl‐Type Structure for Room‐Temperature Refrigeration - Zhang, Yikun; Hao, Weixiang; Hu, Chenglong; Wang, Xing; Zhang, Xuefeng; Li, Lingwei (Advanced functional materials, 2023)
Magnetic refrigeration technology based on the magnetocaloric effect (MCE) of magnetic substances has been considered a prominent, energy‐efficient, and environmentally benign cooling method. Exploring suitable magnetic substances is a prerequisite for practical applications. A family of rare‐earth‐free magnetocaloric materials called Mn30Fe20−xCuxAl50 alloys is identified room‐temperature refrigeration, which are derived from the well‐known MnAl‐based permanent magnets. As expected from experimental and theoretical investigations, all of the Mn30Fe20−xCuxAl50 alloys are crystallized in a stable cubic CsCl‐type crystal structure, revealing a single second‐order type magnetic phase transition (MPT) with tunable MPT temperature. They also exhibit a large reversible MCE and good magnetocaloric performances in a wide temperature range. Crucially, these Mn30Fe20−xCuxAl50 alloys represent a rare case of magnetic materials belonging to a large family that can be fabricated from low‐price, earth‐abundant, and non‐toxic elements. They could provide new choices for practical room‐temperature magnetic refrigeration applications. The achievement of good magnetocaloric performances is reported in the Mn30Fe20‐xCuxAl50 alloys with a stable cubic CsCl‐type structure which are derived from the family of MnAl‐based permanent magnets. These alloys represent a rare case of magnetocaloric materials that can be fabricated from low‐price, earth‐abundant, and non‐toxic elements, which could provide new choices for room‐temperature refrigeration.